Conceptualising paranoia in ASD: A systematic review and development of a theoretical framework. (May 2016) - Spain, Debbie; Sin, Jacqueline; Freeman, Daniel
Highlights: Psychosocial factors may render individuals with ASD vulnerable to developing paranoia. Seven cross-sectional studies have examined paranoia in ASD. Levels of paranoia are higher in ASD, compared to typically-developing samples. ASD traits and neuropsychological functioning may precipitate and perpetuate paranoia. A framework outlining causal and maintaining factors for paranoia in ASD is proposed. Abstract: Paranoia, unfounded ideation that others deliberately intend harm, has predominately been studied in schizophrenia. Increasingly, it is recognised that there is a spectrum of severity of excessive mistrust across the general population. Relatively little is known about paranoia in individuals with autism spectrum disorders (ASD), but rates could be expected to be higher given both difficulties in understanding others' mental states and frequent experiences of negative social interactions. A systematic search of English-language peer-reviewed publications was undertaken to synthesise empirical research about paranoia in ASD. Seven studies, comprising a total of 180 ASD participants, met the inclusion criteria. All the studies were cross-sectional, thereby limiting causal interpretations. Individuals with ASD were consistently found to have higher levels of paranoia compared to non-clinical controls, and lower levels than individuals with current psychotic experiences manifesting in the context of schizophrenia. Furthermore, the initial evidence indicates that paranoia in ASD may be linked with theory of mind performance, negative affect, and jumping to conclusions, but not to attributional style. As in typically-developing populations, causal and maintaining mechanisms for paranoia in ASD, against a background of genetic and environmental risk, most likely include cognitive and affective processes interacting with social factors. We hypothesise, however, that core ASD characteristics and associated neurocognitive impairments also serve to precipitate and perpetuate paranoia. A framework to guide further investigation is outlined.